Pengaruh IPM, Jumlah Penduduk Dan Upah Terhadap Tingkat Kemiskinan Di Bali Tahun 2018-2021 - Fiqri Febrian Pratama; Siti Aisyah (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2023)
Poverty is one of the problems in a complex and multidimensional economy. Therefore, a solution is needed to overcome and reduce the level of poverty. This study was conducted to analyze the effect of the level of the Human Development Index (HDI), Population and Wages on the poverty level in Bali Province. This observation uses secondary data obtained from the Central Statistics Agency (BPS) of Bali Province. The technique used is a quantitative approach with panel data regression techniques from 2018-2021 with a total of 9 districts/cities of observation data and processed with a Fixed Effect Model (FEM) approach using Eviews 10. The final calculation results show that the variable Human Development Index and Wages have a significant effect on Poverty in the Province of Bali in 2018-2021. This research is expected to be taken into consideration in decision making for the central and local governments in dealing with the problem of poverty in the province of Bali